Nutrición enteral por sonda nasogástrica como factor de riesgo y pronóstico de neumonía asociada al ictus - Llaja Reaño, Juan Victor (2022)
Stroke-associated pneumonia (SAP) is the most frequent complication after stroke increasing mortality and morbidity. It occurs in the first 7 days after stroke. The nasogastric tube (NGT) is used to prevent this complication, however there is controversy about its role. Our aim was to identify whether enteral nutrition by NGT is a risk and prognostic factor for stroke-associated pneumonia. Methods: Bibliographic review of studies published in databases on the pathophysiology of SAP, the prevalence of SAP, the role of NGT in the development of SAP and its influence on prognosis, evaluating the quality of evidence. Results: SAP develops due to immunodeficiency associated with stroke and aspiration. The presence of NGT increases the prevalence of SAP due to bacterial colonization and other complementary interventions are needed to reduce its prevalence and improve prognosis based on moderate to high quality evidence. Discussion: There are meta-analyses that support our results such as the increased risk of acquiring SAP and increased mortality Conclusions: NGT is not a sufficient intervention to exert a protective role in stroke patients.